Book Review: Leona M. English and Catherine J. Irving (2015), Feminism in Community: Adult Education for Transformation (Concept: The Journal of Contemporary Community Education Practice Theory, 2016)
This is the kind of book that ignites your spirit when you are assailed on all sides with neo-liberal agendas. These agendas convey messages about ‘value for money’ education, labour activation, economic development, all of which took centre stage in adult education in Ireland over the past few years. Leona English and Catherine Irving succeed in shifting the lens away from the pure marketisation of the field towards a more enriching, politically aware and egalitarian focus. They identify the gap in the literature on women and learning and the intersection of race, ethnicity, class and gender. In the wider debates on equality, women as a category have become increasingly invisible, but even more worryingly, the authors maintain that there is a general dilution of previously powerful pedagogies in favour of more superficial, short-term and individualised outcomes. For example, while we have interrogated the notion of empowerment for many years, at least the concept was and is about power. Now, however, this concept is reduced to ephemeral, almost inconsequential ideas about self-esteem and confidence, devoid of social and gender analysis. This is a very long way from the political aims of feminism, yet it dominates many public and media discussions on the status of women.